Repeatable Passive Fiber Optic Coupling of Single-Mode Waveguides in High-Precision Disposable Photonic Biosensors - Reck, Jakob; von Emden, Laurids; Mihov, Klara; Kresse, Martin; Weigel, Madeleine; Qian, Tianwen; Keuer, Csongor; Winklhofer, Philipp; Amberg, Marcel; de Felipe, David; Zawadzki, Crispin; Kleinert, Moritz; et al. (Photonics, 2024)
This research demonstrates a method for the repeatable passive fiber optic coupling of single-mode waveguides with a micron-scale accuracy for high-precision disposables. The aim is to broaden the application of photonic integrated circuits (PICs) from traditional fiber optic communication systems to include medical, life science, and environmental sensing applications. The proposed passive coupling system enables the straightforward and reliable interchange of disposable photonic chips without manual read-out unit adjustments. Robustness is attributed to the chip-side grating couplers with 3 dB coupling tolerances exceeding ± 25 µm and a mechanical three-groove kinematic method ensuring precise alignment. The system simplicity is highlighted by the simple manual insertion and fixation of silicon nitride (Si3N4) PICs on a carrier using magnetic force and passive alignment features. Testing on a batch of 99 identical yet independent units revealed a standard deviation (SD) of 5.1 dB in coupling loss, without realignment post-calibration. This eliminates the need for active alignment processes, showing its potential for enabling field use. A usability assessment with five untrained operators confirms the suitability for various end-users, with consistent performance in engaging and disengaging disposable PICs. The research significantly advances the integration of photonic sensor technology into practical applications, particularly for chemical and biological fluid analysis in point-of-care settings.